2012
DOI: 10.1039/c1fd00051a
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquids studied across different scales: A computational perspective

Abstract: For theoreticians, ionic liquids represent a major challenge. This is due to the fact that intermolecular interactions are particularly strong because of ionic liquids' ionicity. This, in turn, causes a subtle interplay between different scales which is encoded in the measured macro- and mesoscopic properties and also in the molecular electrostatic characteristics. Therefore, force fields have to describe the microscopic processes correctly in order to reproduce macroscopic properties accurately over a large r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
114
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(117 citation statements)
references
References 116 publications
(176 reference statements)
3
114
0
Order By: Relevance
“…Several studies showed that ions constituting ILs have non-integer charges. [52][53][54][55] Furthermore, bonding within the ion pair in ILs is not purely electrostatic but exhibits considerable amounts of dispersive interactions. [56,57] Thus, the treated species are not ions in the classical sense but may be regarded as "quasi-ions" or "effective ions".…”
Section: Ion Volume Partitioning Of V Vdwrmentioning
confidence: 99%
“…Several studies showed that ions constituting ILs have non-integer charges. [52][53][54][55] Furthermore, bonding within the ion pair in ILs is not purely electrostatic but exhibits considerable amounts of dispersive interactions. [56,57] Thus, the treated species are not ions in the classical sense but may be regarded as "quasi-ions" or "effective ions".…”
Section: Ion Volume Partitioning Of V Vdwrmentioning
confidence: 99%
“…[35][36][37][38][39][40][41][42][43] Various simulation methods are available at different length and time scales depending on the specific targets requested from the studied IL systems. [35][36][37][38][39][40][41][42][43] Various simulation methods are available at different length and time scales depending on the specific targets requested from the studied IL systems.…”
Section: Introductionmentioning
confidence: 99%
“…We find that for a given cation, ILs having a [CNPyr] anion have the fastest dynamics, followed by those with a [124triz] anion. Those with the small spherical [PF 6 ] anion actually had the slowest dynamics.…”
mentioning
confidence: 99%